A new Sliding Mode Control tuning approach for second-order inverse-response plus variable dead time processes. (July 2022) - Castellanos-Cárdenas, Duby; Castrillón, Fabio; Vásquez, Rafael E.; Posada, Norha L.; Camacho, Oscar
Abstract: This work addresses a new set of tuning rules for Sliding Mode Control (SMC) applied to second-order inverse-response plus variable dead time processes. Descriptions of the dynamics of inverse response systems and sliding-mode controllers are first provided. Then, we present the design process for the set of SMC tuning rules, using dimensional analysis, experimental design, optimization, and model reduction techniques for set-point tracking. The obtained expressions are simple, which eases the application of the proposed step-by-step systematic methodology. The performance and robustness of the proposed SMC tuning method are compared to other well-known controllers, and then applied to a Van de Vusse isothermal reactor, which is a complex nonlinear second-order inverse-response system that exhibits variable dead time. The performance achieved with the new SMC tuning method is good for set-point tracking, while exhibiting a good behavior for disturbance rejection, and can be applied considering a wide-range of parameters of the process' transfer function. Graphical abstract: Highlights: New step-by-step Sliding Mode Control (SMC) tuning approach. The method uses simple expressions to facilitate the application. The new SMC tuning method is good for set-point tracking and disturbance rejection. Application for a nonlinear second-order inverse-response system with variable dead time.